Mehrsprachigkeit und Schulerfolg – die europäische (deutsche) Perspektive - Altmayer, Claus (Stellenbosch Papers in Linguistics Plus, 2012)
Multilingualism and multilingual education in Africa are different from multilingualism and multilingual education in Europe. Nevertheless, to some extent the circumstances are comparable. In both regions there are currently important academic and political discussions about the significance of the first language in the process of second language acquisition and about the effectiveness of bilingual education. Against this background the paper outlines the discussions in Germany about the impact "mother tongue education" may have on the acquisition of a second language (German), on the one hand, and on the different models of bilingual education, on the other hand, especially with regard to migrant contexts. There is some research on these topics, but more empirical evidence is urgently needed, in Europe as well as Africa. Keywords Schlüsselbegriffe: Mehrsprachigkeit, Migration, Muttersprache-unterricht, Herkunftssprache, bilingualer Unterricht, Interdependenzhypothese, konzeptionelle Schriftlichkeit : multiligualism, migration, mother tongue education, language of origin, bilingual education, interdependece hypothesis, conceptual writing